A day of cultural exchange - discover the beauty of the Prophet’s language - Jamilah Bebe, Mohamad; Nursyaheedah, Muhammad Isa; Rosjuliana Hidayu, Rosli (Pejabat Naib Canselor, 2016)
Centre for Modern Languages & Human Sciences (CMLHS), Universiti Malaysia Pahang (UMP) organised an educational programme with Arabic elements involving secondary students from Sekolah Menengah Agama Al-Maarif, an excellent cluster school.